Effectiveness and safety of ombitasvir/paritaprevir/ritonavir in treatment of chronic hepatitis C Egyptian hemodialysis patients, case-control study - Nahla Mohamed Teama; Waleed Anwar Abdel-Mohsen; Ossama Ashraf Ahmed; Sarah Mohamed El Sayed; Ahmed Mohamed ElGhandour (Egyptian Liver Journal, 2021)
Abstract Background Prevalence of hepatitis C virus infection in patients with renal diseases is higher compared to the general population. FDA has approved ombitasvir/paritaprevir/ ritonavir for the treatment of patients with severe renal disease. This study aimed to evaluate the efficacy and safety of ombitasvir/paritaprevir/ritonavir with or without ribavirin in treatment of chronic hepatitis C Egyptian hemodialysis patients to compare it with the same treatment result in chronic hepatitis C Egyptian patients with normal renal functions. This case-control study was conducted on one hundred patients with confirmed diagnosis of HCV-positive infection at the Center of National Committee for Control of Viral Hepatitis [NCCVH] at Ain Shams University Hospital. Patients were divided into two groups: group I (control group) with 50 chronic hepatitis C virus patients with normal renal functions and group II (Case Group) with 50 chronic hepatitis C virus hemodialysis patients. Results 95.1% of prevalent hemodialysis patients achieved sustained virological response (SVR), while 100% of patients with normal kidney functions achieved sustained virological response. Most common side effects were hemoglobin drop, gastrointestinal disturbance, severe fatigue, and itching. Conclusion Ombitasvir, paritaprevir, and ritonavir are considered a safe and effective in treatment in HCV infection in patients on regular hemodialysis as in chronic hepatitis C virus infection patients with normal kidney functions.